A cellulose / acrylamide ultra-stretchable, adhesive hydrogel and preparation method thereof
By introducing acrylamide monomers into cellulose hydrogels and polymerizing them, the problem of insufficient flexibility and ductility of cellulose hydrogels was solved, and a cellulose/acrylamide hydrogel with ultra-tensioning properties and good adhesion was prepared, which enhanced its application potential in medical materials.
Patent Information
- Application Number
- CN202211638053.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-16
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-12-16
AI Technical Summary
Existing cellulose hydrogels have shortcomings in flexibility and ductility, and are usually not self-adhesive, limiting their application potential in medical materials.
Cellulose/acrylamide superstretched, adherent hydrogel was prepared by stirring and mixing functional cellulose nanoparticles with acrylamide monomer at a specific concentration ratio and temperature conditions, and adding a heat initiator for polymerization.
The hydrogel prepared has good tensile properties, stretches to 30 times the initial length and can recover within 2 minutes, has good adhesion and repeatability, and has excellent mechanical properties.
Smart Images

Figure CN115746208B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material preparation, and in particular relates to a cellulose / acrylamide ultra-stretchable and adhesive hydrogel and a preparation method thereof. Background Art
[0002] In recent years, with the increasing depletion of petroleum fossil resources and the increasingly serious environmental pollution, the development of renewable biomass resources has received widespread attention. As an important green biomass resource, cellulose has been widely studied by the industry and basic research fields. Cellulose is the most abundant natural polymer in nature. In general, the cellulose content in wood accounts for about 40-50%, and the cellulose content in cotton is as high as more than 90%. Due to its renewable, biocompatible and biodegradable characteristics, it is widely used in the preparation of membrane materials, nano-microspheres and hydrogels. Therefore, it is in line with the idea of sustainable development and the needs of renewable resource strategies to focus on the fine processing of cellulose and develop cellulose-based functional materials with high added value and high performance. As a highly water-absorbent and high-water-retaining material, hydrogels are widely used in many fields, such as tissue engineering scaffolds, wound dressings, facial masks, thickeners, drug carriers, agricultural films, etc. CN 113185641A discloses a functional cellulose-based nanoparticle and its green preparation method and application. The prepared cellulose-based nanoparticle solution is used as a crosslinking agent, mixed with a monomer and a thermal initiator, and fully stirred and dissolved. The mixture is polymerized at 70-90°C for 50-60 minutes. After the reaction is completed, a hydrogel with the cellulose-based nanoparticle solution as a crosslinking agent is obtained. However, due to the presence of a large number of hydroxyl groups on the cellulose molecular chain, the hydrogen bond network formed between the hydroxyl groups makes the cellulose molecular chain rigid, so that the synthesized cellulose hydrogel generally has the disadvantages of poor flexibility and ductility; in addition, the hydrogel usually does not have self-adhesion and needs to be fixed with auxiliary means, which will cause some side effects during application and significantly limit its application potential as a medical material. Summary of the invention
[0003] In view of the above problems existing in the prior art, the first technical problem to be solved by the present invention is to provide a method for preparing a cellulose / acrylamide ultra-stretchable and adhesive hydrogel. Another technical problem to be solved by the present invention is to provide a cellulose / acrylamide ultra-stretchable and adhesive hydrogel prepared by the method.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing a cellulose / acrylamide ultra-stretchable and adhesive hydrogel comprises the following steps: stirring and mixing functional cellulose nanoparticles and monomer acrylamide at a concentration ratio of 0.02-0.2wt%:0.7-1.4mol / L at room temperature, then adding a thermal initiator in an amount of 0.05-0.2mol / % of the monomer, stirring and mixing to obtain a cellulose / acrylamide mixed solution, and polymerizing the cellulose / acrylamide mixed solution at 40-70°C for 2-48h to obtain a cellulose / acrylamide ultra-stretchable and adhesive hydrogel.
[0006] Furthermore, the functional cellulose nanoparticles and the monomer acrylamide were stirred and mixed at room temperature at a concentration ratio of 0.02 wt %: 1.4 mol / L.
[0007] Furthermore, the cellulose / acrylamide mixed solution is polymerized at 40° C. for 2 to 48 hours to obtain the cellulose / acrylamide ultra-stretchable and adhesive hydrogel.
[0008] Preferably, the cellulose / acrylamide mixed solution is polymerized at 40° C. for 48 hours to obtain the cellulose / acrylamide ultra-stretchable and adhesive hydrogel.
[0009] Furthermore, the functional cellulose nanoparticles are prepared by dissolving microcrystalline cellulose in a NaOH / urea aqueous solution with a mass ratio of NaOH, urea and water of 7:12:100, freezing at -29°C for 24 to 48 hours, and then shearing at 2000 rpm for 5 to 10 minutes to obtain a cellulose solution; dropping monomer allyl glycidyl ether into the cellulose solution, reacting at room temperature, and obtaining self-assembly by dialysis after the reaction is completed.
[0010] Furthermore, the mass fraction of cellulose in the cellulose solution is 4 wt %, the molar ratio of the monomer allyl glycidyl ether to the glucose unit in microcrystalline cellulose is 1.0-2.0, and the dialysis is performed for 4 days until the deionized water is neutral.
[0011] Furthermore, the functional cellulose nanoparticles and the monomer acrylamide are stirred and mixed at room temperature for 30 minutes at a concentration ratio of 0.02-0.2 wt%: 0.7-1.4 mol / L.
[0012] Further, the mixture was stirred for 5 minutes to obtain a cellulose / acrylamide mixed solution.
[0013] Furthermore, the thermal initiator is selected from one of ammonium persulfate, potassium persulfate, and azobisisobutylamidine hydrochloride.
[0014] Furthermore, the monomer used in the present application is acrylamide, and acrylic acid, acrylamide / acrylic acid, polyethylene glycol methyl ether methacrylate, methoxy polyethylene glycol acrylate, N-hydroxyethyl acrylamide, 3-sulfopropyl acrylate, and acryloyloxyethyl trimethyl ammonium chloride can be selected according to actual needs as monomers that can also form a polymer grid.
[0015] The cellulose / acrylamide ultra-stretchable and adhesive hydrogel prepared by the above method.
[0016] Furthermore, the stretched length of the hydrogel is 1-30 times of the initial length, and when the stretched length of the hydrogel is 30 times of the initial length, the time to recover to the initial length is less than 2 minutes.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] Based on the functional cellulose-based nanoparticles prepared by the prior art, the present application reduces the monomer concentration, reduces the polymerization temperature, and increases the polymerization time. The prepared cellulose / acrylamide hydrogel has good tensile properties and can be stretched to 30 times of the initial length and recover within 2 minutes; it has good adhesion, the 180° peel strength is 19.5N / m, and it has repeatable adhesion. After repeated peeling, its 180° peel strength does not change significantly; and after repeated adhesion and peeling, no residue is found; it has good mechanical properties, the tensile strain can reach 4739%, and the tensile strength can reach 177kPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The figure is the effect of different polymerization times on the tensile stress-strain curve of cellulose / acrylamide hydrogel in Example 1, Example 2 and Example 3;
[0020] Figure 2 The influence diagram of different monomer concentrations on the tensile stress-strain curve of cellulose / acrylamide hydrogel in Example 1 and Example 4;
[0021] Figure 3 is a 180° peel strength curve of the cellulose / acrylamide hydrogel prepared in Example 4;
[0022] Figure 4 Figure 4 is the adhesion and peeling diagram of the cellulose / acrylamide hydrogel prepared in Example 4 on the nitrile gloves;
[0023] Figure 5 The diagram shows the adhesion of the cellulose / acrylamide hydrogel prepared in Example 4 on the surfaces of various materials. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, the modification or replacement of the inventive method, step or condition, all belong to the scope of the present invention. In the following examples, if there is no special explanation, the technical means used in the examples are conventional means well known to those skilled in the art.
[0025] Example 1
[0026] A method for preparing a cellulose / acrylamide ultra-stretchable and adhesive hydrogel comprises the following steps:
[0027] (1) 7 g of NaOH, 12 g of urea solution and 100 g of water were mixed and stirred at room temperature until they were completely dissolved to obtain System 1.
[0028] (2) 4 g of microcrystalline cellulose was added to system 1, dispersed evenly, and frozen at -29°C for 12 h. After freezing, the mixture was sheared at 2000 rpm for 5 min to obtain system 2.
[0029] (3) At room temperature, allyl glycidyl ether (AGE) with a molar ratio of 1.4 to glucose units in microcrystalline cellulose was added dropwise to system 2 and reacted for 8 h to obtain system 3.
[0030] (4) The system 3 was transferred into a dialysis bag and dialyzed in deionized water until it became neutral, thereby obtaining functional cellulose nanoparticles.
[0031] (5) 0.02 wt % of the functional cellulose nanoparticles obtained in step (4) and 1.4 M acrylamide were added to water in sequence and stirred at room temperature for 30 min to obtain system 4.
[0032] (6) Add 0.05 mol% ammonium persulfate (ammonium persulfate / acrylamide) to system 4 and stir for 5 minutes to obtain system 5.
[0033] (7) Pour the system 5 obtained in step (6) into a mold and heat at 40° C. for 12 h for polymerization to obtain a cellulose / acrylamide ultra-stretchable and adhesive hydrogel.
[0034] like Figure 1 , Figure 2 As shown, the tensile stress of the hydrogel prepared in Example 1 is 116 kPa and the strain is 3835%.
[0035] Example 2
[0036] A method for preparing a cellulose / acrylamide ultra-stretchable and adhesive hydrogel comprises the following steps:
[0037] (1) 7 g of NaOH, 12 g of urea solution and 100 g of water were mixed and stirred at room temperature until they were completely dissolved to obtain System 1.
[0038] (2) 4 g of microcrystalline cellulose was added to system 1, dispersed evenly, and frozen at -29°C for 12 h. After freezing, the mixture was sheared at 2000 rpm for 5 min to obtain system 2.
[0039] (3) At room temperature, allyl glycidyl ether (AGE) with a molar ratio of 1.4 to glucose units in microcrystalline cellulose was added dropwise to system 2 and reacted for 8 h to obtain system 3.
[0040] (4) The system 3 was transferred into a dialysis bag and dialyzed in deionized water until it became neutral, thereby obtaining functional cellulose nanoparticles.
[0041] (5) 0.02 wt % of the functional cellulose nanoparticles obtained in step (4) and 1.4 M acrylamide were added to water in sequence and stirred at room temperature for 30 min to obtain system 4.
[0042] (6) Add 0.05 mol% ammonium persulfate (ammonium persulfate / acrylamide) to system 4 and stir for 5 minutes to obtain system 5.
[0043] (7) Pour the system 5 obtained in step (6) into a mold and heat at 40° C. for 24 h for polymerization to obtain a cellulose / acrylamide ultra-stretchable and adhesive hydrogel.
[0044] like Figure 1 As shown, the tensile stress of the hydrogel prepared in Example 2 is 161 kPa and the strain is 3695%.
[0045] Example 3
[0046] A method for preparing a cellulose / acrylamide ultra-stretchable and adhesive hydrogel comprises the following steps:
[0047] (1) 7 g of NaOH, 12 g of urea solution and 100 g of water were mixed and stirred at room temperature until they were completely dissolved to obtain System 1.
[0048] (2) 4 g of microcrystalline cellulose was added to system 1, dispersed evenly, and frozen at -29°C for 12 h. After freezing, the mixture was sheared at 2000 rpm for 5 min to obtain system 2.
[0049] (3) At room temperature, allyl glycidyl ether (AGE) with a molar ratio of 1.4 to glucose units in microcrystalline cellulose was added dropwise to system 2 and reacted for 8 h to obtain system 3.
[0050] (4) The system 3 was transferred into a dialysis bag and dialyzed in deionized water until it became neutral, thereby obtaining functional cellulose nanoparticles.
[0051] (5) 0.02 wt % of the functional cellulose nanoparticles obtained in step (4) and 1.4 M acrylamide were added to water in sequence and stirred at room temperature for 30 min to obtain system 4.
[0052] (6) Add 0.05 mol% ammonium persulfate (ammonium persulfate / acrylamide) to system 4 and stir for 5 minutes to obtain system 5.
[0053] (7) Pour the system 5 obtained in step (6) into a mold and heat at 40° C. for 48 h for polymerization to obtain a cellulose / acrylamide ultra-stretchable and adhesive hydrogel.
[0054] like Figure 1 As shown, the tensile stress of the hydrogel prepared in Example 1 is 177 kPa and the strain is 4739%.
[0055] Example 4
[0056] A method for preparing a cellulose / acrylamide ultra-stretchable and adhesive hydrogel comprises the following steps:
[0057] (1) 7 g of NaOH, 12 g of urea solution and 100 g of water were mixed and stirred at room temperature until they were completely dissolved to obtain System 1.
[0058] (2) 4 g of microcrystalline cellulose was added to system 1, dispersed evenly, and frozen at -29°C for 12 h. After freezing, the mixture was sheared at 2000 rpm for 5 min to obtain system 2.
[0059] (3) At room temperature, allyl glycidyl ether (AGE) with a molar ratio of 1.4 to glucose units in microcrystalline cellulose was added dropwise to system 2 and reacted for 8 h to obtain system 3.
[0060] (4) The system 3 was transferred into a dialysis bag and dialyzed in deionized water until it became neutral, thereby obtaining functional cellulose nanoparticles.
[0061] (5) 0.02 wt % of the functional cellulose nanoparticles obtained in step (4) and 1 M acrylamide were added to water in sequence and stirred at room temperature for 30 min to obtain system 4.
[0062] (6) Add 0.05 mol% ammonium persulfate (ammonium persulfate / acrylamide) to system 4 and stir for 5 minutes to obtain system 5.
[0063] (7) Pour the system 5 obtained in step (6) into a mold and heat at 40° C. for 12 h for polymerization to obtain a cellulose / acrylamide ultra-stretchable and adhesive hydrogel.
[0064] like Figure 2 As shown, the tensile stress of the hydrogel obtained in Example 4 is 113 kPa and the strain is 4445%.
[0065] like Figure 3 As shown, the five 180° peel strengths of the hydrogel prepared in Example 4 were 18.9 N / m, 19.5 N / m, 19.2 N / m, 18.7 N / m and 19.3 N / m, respectively. It has repeatable adhesion, and its 180° peel strength does not change significantly after repeated peeling.
[0066] like Figure 4 , Figure 5 As shown, the hydrogel can adhere to a variety of materials, including rubber, metal, plastic, wood, glass and polytetrafluoroethylene materials, and no residue is found when the hydrogel is repeatedly adhered to and then peeled off from a hand wearing nitrile gloves.
[0067] Example 5
[0068] A method for preparing a cellulose / acrylamide ultra-stretchable and adhesive hydrogel comprises the following steps:
[0069] (1) 7 g of NaOH, 12 g of urea solution and 100 g of water were mixed and stirred at room temperature until they were completely dissolved to obtain System 1.
[0070] (2) 4 g of microcrystalline cellulose was added to system 1, dispersed evenly, and frozen at -29°C for 12 h. After freezing, the mixture was sheared at 2000 rpm for 8 min to obtain system 2.
[0071] (3) At room temperature, allyl glycidyl ether (AGE) with a molar ratio of 1.4 to glucose units in microcrystalline cellulose was added dropwise to system 2 and reacted for 8 h to obtain system 3.
[0072] (4) The system 3 was transferred into a dialysis bag and dialyzed in deionized water until it became neutral, thereby obtaining functional cellulose nanoparticles.
[0073] (5) 0.2 wt % of the functional cellulose nanoparticles obtained in step (4) and 1 M acrylamide were added to water in sequence and stirred at room temperature for 30 min to obtain system 4.
[0074] (6) Add 0.1 mol% ammonium persulfate (ammonium persulfate / acrylamide) to system 4 and stir for 5 minutes to obtain system 5.
[0075] (7) Pour the system 5 obtained in step (6) into a mold and heat at 50° C. for 10 h to polymerize, thereby obtaining a cellulose / acrylamide ultra-stretchable and adhesive hydrogel.
[0076] Example 6
[0077] A method for preparing a cellulose / acrylamide ultra-stretchable and adhesive hydrogel comprises the following steps:
[0078] (1) 7 g of NaOH, 12 g of urea solution and 100 g of water were mixed and stirred at room temperature until they were completely dissolved to obtain System 1.
[0079] (2) 4 g of microcrystalline cellulose was added to system 1, dispersed evenly, and frozen at -29°C for 48 h. After freezing, the mixture was sheared at 2000 rpm for 10 min to obtain system 2.
[0080] (3) At room temperature, allyl glycidyl ether (AGE) with a molar ratio of 2.0 to glucose units in microcrystalline cellulose was added dropwise to system 2 and reacted for 8 h to obtain system 3.
[0081] (4) The system 3 was transferred into a dialysis bag and dialyzed in deionized water until it became neutral, thereby obtaining functional cellulose nanoparticles.
[0082] (5) 0.02 wt % of the functional cellulose nanoparticles obtained in step (4) and 1 M acrylamide were added to water in sequence and stirred at room temperature for 30 min to obtain system 4.
[0083] (6) Add 0.2 mol% ammonium persulfate (ammonium persulfate / acrylamide) to system 4 and stir for 5 minutes to obtain system 5.
[0084] (7) Pour the system 5 obtained in step (6) into a mold and heat at 60° C. for 8 h for polymerization to obtain a cellulose / acrylamide ultra-stretchable and adhesive hydrogel.
[0085] Comparative Example 1
[0086] A hydrogel using a cellulose-based nanoparticle solution as a crosslinking agent comprises the following steps:
[0087] (1) 7 g of NaOH, 12 g of urea solution and 100 g of water were mixed and stirred at room temperature until completely dissolved to obtain system 1;
[0088] (2) Weigh 4 g of dry microcrystalline cellulose and add it to system 1. After uniform dispersion, freeze it at -29°C for 48 h. After freezing, shear it at 2000 rpm for 5 min to obtain system 2.
[0089] (3) Allyl glycidyl ether (AGE) in a molar ratio of 1.4 to glucose units in microcrystalline cellulose was added dropwise to system 2 at room temperature, and the mixture was stirred for a sufficient reaction for 8 hours to obtain system 3.
[0090] (4) The system 3 was transferred into a dialysis bag and dialyzed in deionized water until it became neutral, thereby obtaining functional cellulose nanoparticles.
[0091] (5) 0.001% of the cellulose-based nanoparticles obtained in step (4) and 2.8 M acrylamide were added to water in sequence and stirred at room temperature for 30 min to obtain system 4.
[0092] (6) Add 0.049% ammonium persulfate (ammonium persulfate / acrylamide) to system 4 and stir for 5 minutes to obtain system 5.
[0093] (7) Pour the system 5 obtained in step (6) into a mold and polymerize at 80° C. for 55 min. After the polymerization reaction is completed, a hydrogel with the cellulose-based nanoparticle solution as a crosslinking agent is obtained.
[0094] The hydrogel with functional cellulose-based nanoparticles as cross-linkers has a strength of 1.46 MPa at 80% strain.
[0095] Comparative Example 2
[0096] (1) 1.4 M acrylamide and 0.06 mol % N,N-methylenebisacrylamide were added to water in sequence and stirred at room temperature for 30 min to obtain system 1.
[0097] (2) Add 0.049 mol% ammonium persulfate (ammonium persulfate / acrylamide) to system 1 and stir for 5 minutes to obtain system 2.
[0098] (3) Pour the system 2 obtained in step (2) into a mold and polymerize at 50° C. for 12 h. After the polymerization reaction is completed, a hydrogel with N,N-methylenebisacrylamide as a crosslinking agent is obtained.
[0099] The tensile strength of the hydrogel using N,N-methylenebisacrylamide as the cross-linker was 206 kPa and the strain was 578%.
Claims
1. A method for preparing a cellulose / acrylamide ultra-stretchable, adhesive hydrogel, comprising the following steps: (1) Mix 7 g of NaOH, 12 g of urea solution and 100 g of water and stir at room temperature until completely dissolved to obtain system 1; (2) Add 4 g of microcrystalline cellulose to system 1, disperse it evenly and freeze it at -29 °C for 12 h. After freezing, shear it at 2000 rpm for 5 min to obtain system 2. (3) adding allyl glycidyl ether at a molar ratio of 1.4 to glucose units in microcrystalline cellulose to system 2 at room temperature and reacting for 8 h to obtain system 3; (4) Transferring system 3 to a dialysis bag and dialyzing it in deionized water until it becomes neutral, thereby obtaining functional cellulose nanoparticles; (5) 0.02 wt% of the functional cellulose nanoparticles obtained in step (4) and 1.4 M acrylamide were added to water in sequence and stirred at room temperature for 30 min to obtain system 4; (6) Add 0.05 mol% ammonium persulfate to system 4 and stir for 5 min to obtain system 5; (7) Pour the system 5 obtained in step (6) into a mold and heat at 40 °C for 48 h for polymerization to obtain a cellulose / acrylamide ultra-stretchable and adhesive hydrogel.
2. The method for preparing the cellulose / acrylamide ultra-stretchable and adhesive hydrogel according to claim 1, characterized in that: The stretched length of the hydrogel was 1-30 times of its initial length.
3. The method for preparing the cellulose / acrylamide ultra-stretchable and adhesive hydrogel according to claim 2, characterized in that: When the stretched length of the hydrogel was 30 times of its initial length, the time to recover to the initial length was less than 2 min.
Citation Information
Patent Citations
Functional cellulose-based nanoparticles and green preparation method and application thereof
CN113185641A